Nurturing research competence and excellence - Abu Kassim, Noor Lide; Rahman, Mohammad Tariqur (IIUM Press, 2024)
The responsibility for creating and disseminating knowledge has long been placed on higher education institutions, particularly universities. Given this obligation, universities are frequently evaluated based on their capacity to secure grants, conduct research and disseminate knowledge to benefit human welfare and development. Therefore, university students, particularly those required to conduct research as part of their study programme, are expected to be competent in research. This means that they must be equipped with the necessary knowledge, skills, abilities, and attitudes to perform research successfully. Unsurprisingly, one course that is given much emphasis in postgraduate programmes is research methodology, which develops the much-needed competency in research. From master’s to doctoral programmes, research methodology courses are a must. However, these research methodology courses, more often than not, focus on technical skills and methodologies with little emphasis on issues related to morality and ethical standards.